Beneficiary Assessment for Monitoring : The Zambia Social Recovery Project - World Bank (World Bank, Washington, DC, 2012)
Zambia's Social Recovery Fund promotes community-driven infrastructure rehabilitation through microprojects aimed at cushioning vulnerable groups against the negative effects of adjustment. The fund was formed in 1991 as part of the Social Recovery Project, which was designed to build the capacity of local communities and governments to plan, implement, and manage community investments. Since 1992, the fund has used beneficiary assessments to ensure that funded microprojects target the poor (by allowing the poor to set priorities for the fund's support) and improve overall project performance. Originally a monitoring exercise, beneficiary assessments have become a valuable tool for fostering community participation and building in-country capacity in social assessment methodologies.